LESCH – NYHAN SYNDROME (LNS) - THE REVIEW - Daria Madycka; Weronika Skrzypek; Małgorzata Słaboń; Karol Stępniak; Wiktor Telega; Kinga Wnuczek; Joanna Wrona; Aleksandra Kaźmierczyk; Jędrzej Kęsik (International Journal of Innovative Technologies in Social Science, 2025)
Lesch-Nyhan syndrome (LNS) is a rare X-linked disorder caused by mutations in the HPRT1 gene, which encodes an important enzyme in the purine salvage pathway. Symptoms of LNS include dystonia, gout, intellectual disability, and self-harm. Although the disease was described in 1964, it remains unclear how abnormalities in hypoxanthine and guanine recycling can lead to such significant neurological deficits. Several studies have proposed different hypotheses regarding the etiology of the disease and various treatment options have been proposed, but none have led to a satisfactory explanation of the pathophysiology of the disease. New technologies such as sequencing, optogenetics, genome editing, and induced pluripotent stem cells may provide a unique opportunity to map the precise sequential pathways from genotype to disease phenotype.